2021
DOI: 10.1186/s12884-021-04140-6
|View full text |Cite|
|
Sign up to set email alerts
|

Insaka: mobile phone support groups for adolescent pregnant women living with HIV

Abstract: Background Mobile phone-based interventions have been demonstrated in different settings to overcome barriers to accessing critical psychosocial support. In this study, we aimed to assess the acceptability and feasibility of a phone-based, peer-to-peer support group intervention for adolescent pregnant women aged 15–24 years living with HIV in Zambia. Methods Sixty-one consenting participants were recruited from Antenatal Clinics of two large urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Self-efficacy outcomes were assessed in 16 studies 37 41 42 46 48 49 51 53 54 57 58 64 66 69 71 78. Seven studies found positive effects, two studies had mixed findings and seven studies found no significant effect (GRADE certainty of evidence: low).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy outcomes were assessed in 16 studies 37 41 42 46 48 49 51 53 54 57 58 64 66 69 71 78. Seven studies found positive effects, two studies had mixed findings and seven studies found no significant effect (GRADE certainty of evidence: low).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported on the roles of mHealth in social support from other sources (eg, family, friends and online community) 37 38 41 43 56 67 69 74 78 79. Six studies found a positive effect, while three reported mixed findings and one study reported no significant effect (GRADE certainty of evidence: low).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Text messaging was recommended to provide family planning information to adolescent and young adult women in Sierra Leone [ 16 ]. In Zambia, the Insake mobile phone app provided support to pregnant women living with HIV [ 17 ]. An average of 169 text messages were sent per user.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the affiliations of Nikita Simpson.…”
mentioning
confidence: 99%